1997
DOI: 10.1002/(sici)1096-8628(19970808)71:2<219::aid-ajmg19>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Cervical ribs in fetuses with Ullrich-Turner syndrome

Abstract: The purpose of this study was to analyze the cervical skeleton in fetuses with Ullrich-Turner syndrome (45,X) in a search for skeletal characteristics in the neck region affected by hygroma. In connection with requested autopsies, 9 second trimester human fetuses were investigated radiographically by whole-body and special radiography of the spine. The presence of unilateral or bilateral cervical ribs was a constant finding which seems applicable as a phenotypic characteristic of Ullrich-Turner syndrome. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Scientists found a strong coupling between the abnormality of the vertebral patterns and the amount and strength of associated malformations; that is, the longer the disturbance of the vertebral patterning has lasted, the more associated the malformations have developed and the more the organ systems are affected. According to Kjær and Hansen [19], the presence of unilateral or bilateral cervical ribs was a constant finding which seems applicable as a phenotypic characteristic of Ullrich-Turner syndrome.…”
Section: Embryonic Development Of Cervical Ribsmentioning
confidence: 99%
“…Scientists found a strong coupling between the abnormality of the vertebral patterns and the amount and strength of associated malformations; that is, the longer the disturbance of the vertebral patterning has lasted, the more associated the malformations have developed and the more the organ systems are affected. According to Kjær and Hansen [19], the presence of unilateral or bilateral cervical ribs was a constant finding which seems applicable as a phenotypic characteristic of Ullrich-Turner syndrome.…”
Section: Embryonic Development Of Cervical Ribsmentioning
confidence: 99%
“…No study exists with which the results of this study can be directly compared. In a study by Kjær and Fischer Hansen [1997], UTS fetuses were found to have unilateral or bilateral cervical ribs. In another study by FitzSimmons et al [1994], diminished growth of the long bones (femur, tibia, fibula, humerus, radius, and ulna) was detected by midtrimester in fetuses with UTS.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few investigations have concentrated on skeletal development in UTS fetuses. In one investigation, the appearance of unilateral or bilateral cervical ribs has been described [Kjær and Fischer Hansen, 1997]. Also, the body proportions are different compared to proportions in normal fetal development [FitzSimmons et al, 1994; Andersen et al, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…Other skeletal abnormalities observed are cervical ribs, short metacarpals, genu valgus, mesomelia (leading to short staure), and Madelung deformity (Kjær and Hansen, ; Ranke and Saenger, ). In the embryo, the short stature homeobox gene (SHOX) is expressed in the developing upper and lower limbs, especially at the elbows and knees, as well as the first two pharyngeal arches (Clement‐Jones et al, ).…”
Section: Otolaryngolical/craniofacial/skeletalmentioning
confidence: 99%